Field notes contributed by Beth Proescholdt, December 1, 1981 - Proescholdt, Bethet al (1981)
Field notes were contributed by Beth Proescholdt and other observers. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1981. Epson - sheet feed